Possibilities of the Metaverse for Education: A Retrospective Analysis of Technology Development - Kushnir, Natalia (Educological discourse, 2023)
The rapid development of technologies today is changing the structure of business and production. Already today, the construction of an economy based on the analysis of big data, automation, robotics, the Internet of Things, artificial intelligence, immersive technologies, and blockchain sets new requirements for the qualifications of specialists, significantly changes the essence of certain specialties, and stimulates the emergence of new professions. The gradual integration of these technologies, their further development and the expectation of new technical breakthroughs in the coming years opens up new perspectives and allows developing a conceptual vision of the future reality, which will be a certain combination of the physical and virtual worlds. It is important to understand the current state of technology, which is the basis for building a new reality of the metauniverse. For this, an analysis of publications in the scientometric database Scopus and media devoted to the experience of implementing certain technologies was carried out. The conducted research made it possible to determine that today there is no full implementation of the metauniverse concept. However, the analysis of the current level of technology development, which is the basis for the development of the metauniverse, their interconnection, the degree of interest of business and the authorities of different countries, which is expressed in significant investments in the creation of the metauniverse, is important for its understanding and prediction of the trends of the development of society in the conditions of the metauniverse. All this gives reason to expect the appearance of a working prototype that will be used for communication, conducting business, providing/receiving services, including educational ones.